IMPLEMENTASI METODE OTAK KANAN DALAM PEMBELAJARAN AL- QUR’AN - Iqbal, Muhammad (FORPIM PTKIS ZONA TAPAL KUDA, 2023)
Implementation of the Right Brain Method in Learning the Qur'an, namely teaching that applies the Talaki and classical methods. The purpose of this research is as an effort to find out the implementation and impact of teaching the right brain method at SMP Al Irsyad Banyuwangi. This study uses a mix of quantitative and qualitative methods. Data collection techniques are carried out by means of observation, interviews, and document analysis. The results of this study indicate that the implementation of Al-Qur'an teaching using the right-brain method at SMP Al Irsyad Banyuwangi has two stages, the first stage is the planting of concepts. In this stage, students are required to understand the concept of the main subject directly/using display cards in stages, repeated several times, then randomized. The second stage is the teacher tackling the exercise page on a book or large visual aid. As for the assessment, you can do it by listening, both classically and privately. In these two stages accompanied by the assessment stage, students can already read recitation books according to the correct tajwid rules and can recite them in hijaz tones, namely flat, falling and rising.